Metabolic features of macrophages in inflammatory diseases and cancer. (28th January 2018) - Na, Yi Rang; Je, Sungmo; Seok, Seung Hyeok
Abstract: Macrophages are now considered to be important players in various inflammatory diseases as well as tumor progression. Emerging evidence reveals that macrophage metabolic features are deeply associated with their immune functions. Understanding the interaction between cellular metabolism and immune signaling pathways in macrophages can help us to develop appropriate therapeutic approaches for inflammatory diseases. In this review, we briefly summarize key metabolic features of M1 and M2 macrophages as well as signaling interactions between major metabolic molecules with TLRs and NLRs. Current knowledges of cellular metabolism are focused on macrophages in various disease situations including sepsis, atherosclerosis, obesity, tuberculosis and cancer. Novel insights and present targets for regulating macrophage metabolism are also discussed. Highlights: Pre-established glycolytic capacity determines inflammatory functions of GM-CSF derived macrophages. LPS/IFNγ induces aerobic glycolysis but IL-4/IL-13 potentiates mitochondrial respiration in macrophages. AMPK, mTOR and mitochondrial ROS integrate with pattern recognition receptor signaling pathways. Key metabolic changes of macrophages were reviewed focused on the inflammatory diseases and cancer.